THE RISING IMPORTANCE OF MANDARIN CHINESE, SPANISH, AND ARABIC IN THE GLOBAL ECONOMY - Eshdavlatova Jasmina Akramjon qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
In  an increasingly  multipolar  world,  Mandarin Chinese, Spanish, and  Arabic have emerged as strategically vital languages alongside English. This article examines the economic, demographic, and geopolitical factors driving their growing influence in international trade, investment, and business. It argues that proficiency in these three languages will become a key competitive advantage for individuals, companies, and nations in the 21st-century global economy.